Hear, Hear for Notch: Control of Cell Fates in the Inner Ear by Notch Signaling - Brown, Rogers (Biomolecules, 2020)
The vertebrate inner ear is responsible for detecting sound, gravity, and head motion. These mechanical forces are detected by mechanosensitive hair cells, arranged in a series of sensory patches in the vestibular and cochlear regions of the ear. Hair cells form synapses with neurons of the VIIIth cranial ganglion, which convey sound and balance information to the brain. They are surrounded by supporting cells, which nourish and protect the hair cells, and which can serve as a source of stem cells to regenerate hair cells after damage in non-mammalian vertebrates. The Notch signaling pathway plays many roles in the development of the inner ear, from the earliest formation of future inner ear ectoderm on the side of the embryonic head, to regulating the production of supporting cells, hair cells, and the neurons that innervate them. Notch signaling is re-deployed in non-mammalian vertebrates during hair cell regeneration, and attempts have been made to manipulate the Notch pathway to promote hair cell regeneration in mammals. In this review, we summarize the different modes of Notch signaling in inner ear development and regeneration, and describe how they interact with other signaling pathways to orchestrate the fine-grained cellular patterns of the ear.